Clinical Profile of Bleeding Patterns Among Hemophilia A Patients in East Java, Indonesia - Shanty Larasati, Maria Christina; Endaryanto, Anang; Rianda, Raissa Virgy; Rantam, Fedik Abdul; Ugrasena, I Dewa Gede (Journal of Neonatal Surgery, 2025)
Background: Hemophilia often presents with recurrent and spontaneous hemorrhages, which may involve deep muscles, leading to hematoma formation and hemarthrosis. There is a paucity of evidence regarding bleeding patterns in hemophilia, especially in low- and middle-income countries. This study aimed to describe the bleeding patterns among patients with Hemophilia A. Methods: A cross-sectional study was conducted by collecting data from children with Hemophilia A registered at the Indonesian Hemophilia Society (IHS) in East Java between January 2019 and May 2024. The bleeding patterns analyzed included annualized bleeding rate (ABR) and bleeding types. Results: A total of 71 pediatric patients with Hemophilia A were enrolled: mild (n=19, 27%), moderate (n=50, 70%), and severe (n=2, 3%). The mean patient age was 10 years, and the mean age at diagnosis was 4 years. Hematoma was the initial complaint in approximately 39% of patients. The bleeding types among mild versus moderate hemophilia included gum bleeding (77% vs. 23%), epistaxis (33% vs. 66%), hemarthrosis (50% vs. 50%), intracranial hemorrhage (66% vs. 33%), hematuria (66% vs. 33%), and post-traumatic bleeding (50% vs. 50%). The most frequently affected joints were the knee (75%), ankle (68%), and elbow (66%) across the severity classifications. In patients with mild hemophilia, ABR values were: 12/year (n=9, 47%), 13–24/year (n=5, 26%), and >24/year (n=5, 26%). In moderate hemophilia: 12/year (n=24, 48%), 13–24/year (n=17, 34%), and >24/year (n=9, 18%). In severe hemophilia, ABR was >24/year in both patients (100%). Conclusion: Moderate hemophilia A was more prevalent than mild or severe. Surprisingly, severe bleeding events such as intracranial hemorrhage were more common in the mild group. The ABR was highest among patients with the severe hemophilia A.